2010
DOI: 10.1007/s11434-010-3139-y
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of fluoroquinolone antibiotic gatifloxacin in aqueous solutions

Abstract: Fluoroquinolone antibiotics (FQs) are frequently detected as emerging pollutants in aqueous environments. In this study, kinetics, influencing factors and mechanisms on the photodegradation of gatifloxacin, a representative FQ, were investigated. The photodegradation follows the pseudo-first-order kinetics. Gatifloxacin photodegrades with a quantum yield of (5.94 ± 0.95) × 10 −3 in pure water and undergoes direct photolysis as well as self-sensitized photodegradation. The FQ photodegrades slower in freshwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The degradation process has been referred to as the self-sensitized photooxidation of pollutants [25][26][27]. It is therefore possible that the photodegradation of DCF includes a self-sensitization photooxidation process via •OH, 1 O 2 and O 2 •− under simulated sunlight.…”
Section: Mechanisms and Kinetic Models For The Photodegradation Of Dcfmentioning
confidence: 99%
“…The degradation process has been referred to as the self-sensitized photooxidation of pollutants [25][26][27]. It is therefore possible that the photodegradation of DCF includes a self-sensitization photooxidation process via •OH, 1 O 2 and O 2 •− under simulated sunlight.…”
Section: Mechanisms and Kinetic Models For The Photodegradation Of Dcfmentioning
confidence: 99%
“…In most researches on photo-decomposition of drugs, samples were always confined to diluted solutions (16,17). Most of the degradation processes followed first-order reaction relationship (18), while few (as abeprazole methanolic solutions, 0.8 mg/ mL) showed zero-order kinetics (14).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of biological system, it is difficult to demonstrate clearly the specific role of ROS in the manifestation of phototoxicity in in vivo studies. Drug induced phototoxicity is associated with the formation of toxic photoproducts or the generation of short‐lived intermediates, increased levels of ROS within the skin and may induced skin diseases (41), earlier study of a photosensitive drug under sunlight revealed direct photolysis as well as self‐sensitized photolysis via ˙OH and 1 O 2 (42). Our results demonstrate that LVFX generates 1 O 2 under UV‐R/sunlight exposure which is responsible for photodegradation and photoproducts formation.…”
Section: Discussionmentioning
confidence: 99%